(untitled) (American Journal of Pedagogical and Educational Research, 2024)
In the article, the great thinker Alisher Navoi’s pedagogic views, his content, and the factors of formation of his essence are highlighted. Also, the pedagogical possibilities of using the works of Alisher Navoi were analyzed, and their compatibility with the requirements of today’s times was studied.